2015
DOI: 10.1038/modpathol.2014.61
|View full text |Cite
|
Sign up to set email alerts
|

Napsin A is a specific marker for ovarian clear cell adenocarcinoma

Abstract: Ovarian clear cell adenocarcinoma has a relatively poor prognosis among the ovarian cancer subtypes because of its high chemoresistance. Differential diagnosis of clear cell adenocarcinoma from other ovarian surface epithelial tumors is important for its treatment. Napsin A is a known diagnostic marker for lung adenocarcinoma, and expression of napsin A is reported in a certain portion of thyroid and renal carcinomas. However, napsin A expression in ovarian surface epithelial tumors has not previously been exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 48 publications
6
51
0
Order By: Relevance
“…130 Napsin A is also a useful marker of clear cell carcinomas. 131 ER is positive in most high-grade and low-grade serous carcinomas and endometrioid carcinomas while clear cell carcinomas are usually negative. Some of these markers have helped establish that most neoplasms, which were previously classified as mixed high-grade serous and endometrioid and mixed high-grade serous and clear cell, represent HGSCs with pseudoendometrioid areas and areas of cytoplasmic clearing.…”
Section: Immunohistochemical Markersmentioning
confidence: 99%
“…130 Napsin A is also a useful marker of clear cell carcinomas. 131 ER is positive in most high-grade and low-grade serous carcinomas and endometrioid carcinomas while clear cell carcinomas are usually negative. Some of these markers have helped establish that most neoplasms, which were previously classified as mixed high-grade serous and endometrioid and mixed high-grade serous and clear cell, represent HGSCs with pseudoendometrioid areas and areas of cytoplasmic clearing.…”
Section: Immunohistochemical Markersmentioning
confidence: 99%
“…Recent studies have reported napsin A expression in a subset of ovarian clear cell carcinomas (O-CCCs, 69%-100%) as well as in up to 10% of ovarian and 6%-10% of endometrial (EM) endometrioid carcinomas (EC); in contrast, it is rarely found in high-grade serous carcinoma (HGSC) [7,[9][10][11][12][13]. Napsin A expression in EM-CCC has been observed in 67%-93% of the cases [11,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to SC, CCC do not usually express WT1, p53, and ER. They specifically express napsin A, in contrast to the other EOC [50]. Some studies have shown that the tumor suppressor ARID1A is mutated in almost half of CCC cases [39,51].…”
Section: Clear-cell Carcinomasmentioning
confidence: 99%